Clarifying the information and support needs of family caregivers of nursing home residents with advancing dementia. (May 2021) - Thompson, Genevieve; Hack, Thomas; Rodger, Kerstin; St. John, Phil; Chochinov, Harvey; McClement, Susan
Background: Research has identified inadequacies in the quality and quantity of dementia-related information, particularly end-of-life information provided to those living with dementia and their family caregivers. The purpose of this study was to identify what types of information family caregivers of persons living with dementia in nursing homes would deem useful in preparing them for their relative's end-of-life and assist them to make decisions about care along the dementia trajectory. Methods: The qualitative methodology of interpretive description was used to guide the study in which semi-structured interviews were conducted with nursing home staff in clinical roles (e.g., nurses, health care aides, social workers, speech language pathologists; N = 26), palliative care clinicians ( N = 7), and bereaved family caregivers of persons with dementia ( N = 17). Data were analyzed using thematic analysis. Findings: Eight substantive categories essential to meeting family members' needs for information and preparing them for the future were identified including: (i) dementia in general, (ii) dementia toward the end-of-life, (iii) care of persons dying with dementia, (iv) the role of family caregiver as decision maker, (v) sustaining connection, (vi) emotional impact of dementia on caregivers, (vii) relationships with staff, and (viii) general questions about life in a NH. Conclusion: Our findings suggest that family caregivers of nursing home residents with dementia have unique information and support needs, some disease specific, others more related to life in a nursing home in general. Health care providers need to support and encourage dementia literacy for family caregivers. A key strategy is to proactively broach these topic areas, as too often family caregivers may not recognize or value their need for information.